2015
DOI: 10.5194/tcd-9-1209-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brief Communication: Future avenues for permafrost science from the perspective of early career researchers

Abstract: Abstract. Accelerating climate change and increased economic and environmental interest in permafrost-affected regions have resulted in an acute need for more directed permafrost research. In June 2014, 88 early career researchers convened to identify future priorities for permafrost research. This multidisciplinary forum concluded that five research topics deserve greatest attention: permafrost landscape dynamics; permafrost thermal modelling; integration of traditional knowledge; spatial analysis of permafro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A final limitation of available permafrost hydrogeology models relates to the difficulty of their utility. As noted by Fritz et al (2015), many permafrost heat transfer modeling tools are “too complex to be used by anyone other than modeling experts.” This limitation may help explain the lack of simulations conducted for site‐specific application. Concerted efforts to provide more frequent and detailed model training workshops for interested researchers and develop more user‐friendly model interfaces may help overcome this limitation.…”
Section: Challenges and Opportunities In Hydrogeologic Modeling In Pementioning
confidence: 99%
“…A final limitation of available permafrost hydrogeology models relates to the difficulty of their utility. As noted by Fritz et al (2015), many permafrost heat transfer modeling tools are “too complex to be used by anyone other than modeling experts.” This limitation may help explain the lack of simulations conducted for site‐specific application. Concerted efforts to provide more frequent and detailed model training workshops for interested researchers and develop more user‐friendly model interfaces may help overcome this limitation.…”
Section: Challenges and Opportunities In Hydrogeologic Modeling In Pementioning
confidence: 99%
“…A good example is the surface energy balance included in some of the aforementioned tools. To increase the accessibility of permafrost heat transfer models outside of the modeling expert community, Fritz et al (2015) suggested that “Future research should focus on identifying which processes are most important, so that models with varying levels of complexity can be developed for Arctic stakeholders”. We propose that the same principle should be applied to cold‐regions groundwater models.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…We propose that the same principle should be applied to cold‐regions groundwater models. Our recommendation to modelers is to first focus on identifying the important processes in different environments rather than adding processes to the already complex tools available, and to add varying levels of complexity to their code as suggested by Fritz et al (2015).…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…Other recent international collaborative efforts are the creation of early career researcher (ECR) networks such as PYRN and APECS . These networks have fostered a new generation of permafrost scientists, who started their careers during this expansion of climate change‐motivated permafrost research often in connection with the 4th IPY, in international collaborations through workshops, summer schools, online resources, and ECR‐driven research and outreach projects . The activities of such networks provide opportunities for ECRs to understand early on how to successfully collaborate across national borders and academic systems.…”
Section: Discussionmentioning
confidence: 99%